PERAN PEMBINAAN KEMANDIRIAN DALAM MENGURANGI KASUS RESIDIVIS DI LAPAS NARKOTIKA KELAS IIA JAKARTA - Sianturi, Renaldo; Rachmayanthy, Rachmayanthy (Universitas Nusa Cendana, 2024)
The implementation of the self-reliance coaching program at the Jakarta Class IIA Narcotics Prison in inmate work activities has the hope that the inmate has the skills and can open business opportunities so as not to repeat the criminal act and reduce the recidivism rate. The purpose of this study is to find out the role of fostering independence in efforts to reduce cases of recidivism. The authors used qualitative research methods in this study. The result of this study is that the development of independence in the Jakarta Class IIA Narcotics Prison has been running optimally so that it has a big role in reducing the rate of recidivist cases. Keywords: Coaching; Self-reliance; Recidivist